PENGARUH WORKLIFE BALANCE DAN SPIRITUALITAS DI TEMPAT KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Siti Nur azizah; Muhamad Salim (FEB UNWIKU PURWOKERTO, 2021)
This study aims to analyze the effect of work-life balance, workplace spirituality, on organizational citizenship behavior through organizational commitment to medical personnel at PKU Muhammadiyah Kutowinangun Hospital. The independent variables in this study are worklife balance and spirituality in the workplace, while the dependent variable is organizational commitment and organizational citizenship behavior. The data collection technique in this study is non-probability sampling, where all populations are sampled as many as 38 respondents. The hypothesis was tested with the help of the SPSS 23.0 for windows program. The method used is a quantitative method using path analysis. The test results of the coefficient of determination show that the substructural I value of Adjusted R2 is 0.882, meaning that 88.2% of the organizational commitment variable can be influenced by work-life balance and spirituality in the workplace and 17.8% is influenced by other variables outside the model. Meanwhile, the value of Adjusted R2 substructural II was 0.939, meaning that 93.9% of the variable organizational citizenship behavior was influenced by worklife balance, workplace spirituality, and organizational commitment, and 6.1% was influenced by other variables outside the model. Based on the results of the path analysis and t test that has been carried out, it can be concluded that the high organizational citizenship behavior is influenced by worklife balance, spirituality in the workplace, and commitment. Meanwhile, work-life balance and spirituality in the workplace can have a direct effect on organizational citizenship behavior and organizational commitment can be used as partial intervening variables.